Anemia during pregnancy and adverse maternal outcomes in Georgia–A birth registry-based cohort study - Natia Skhvitaridze; Amiran Gamkrelidze; Tinatin Manjavidze; Tormod Brenn; Erik Eik Anda; Charlotta Rylander (PLoS ONE, 2025)
Background Anemia in pregnancy is an important public health challenge; however, it has not been thoroughly studied in Georgia. We assessed the prevalence of anemia during pregnancy across Georgia and the association between anemia in the third trimester of pregnancy and adverse maternal outcomes. Methods We used data from the Georgian Birth Registry and included pregnant women who delivered between January 1, 2019, and August 31, 2022 (n = 158,668). The prevalence of anemia (hemoglobin (Hb) < 110 g/L) at any time during pregnancy was calculated per region. Pregnant women were classified into anemia severity groups based on their lowest measured Hb values, taking into account the thresholds for each trimester of pregnancy as defined by the WHO recommendations for anemia classification. Adjusted odds ratios (aOR) with 95% confidence intervals (CIs) were calculated for the associations between anemia status and post-delivery intensive care unit (ICU) admission and preterm delivery. Results The prevalence of anemia occurring at least once during pregnancy was 33.1%, with large regional differences in anemia prevalence (19.2%–32.8%). Of 105,811 pregnant women with Hb measurements in the third trimester, 71.0% had no anemia; 20.9%, mild anemia; and 8.1%, moderate or severe anemia. The odds of post-delivery ICU admission did not increase linearly with decreasing Hb value ( P for trend .13), and the relationship was inverse for preterm delivery ( P for trend .01). Conclusions A considerable proportion of pregnant women in Georgia have anemia during pregnancy, and the prevalence and quality of reporting differ across regions. Anemia occurring in the third trimester did not substantially increase the odds of maternal ICU admission or preterm delivery. To progress toward sustainable development goals and alleviate the public health burden of anemia, it is essential to not only identify and manage anemia during pregnancy but also address underlying factors with a multifaceted response.